Cosmic Sex and the Role of Women in Practicing Celibacy (Brahmacharya) to Prevent Violence - Md Amirul Islam; Mst. Baly Khatun (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The purpose of this film review is to investigate the nuanced portrayal of women who are practicing celibacy within the framework of the Indian Bengali film Cosmic Sex. The film explores the transformational role that women adopting celibacy as a spiritual practice might play, as well as the connection between celibacy and the prevention of violence. Through its investigation of cosmic consciousness and sexuality, the film offers a fresh viewpoint on the ways in which women, by adopting Brahmacharya (the concept of celibacy in Hinduism), contribute to the establishment of a harmonious social order. The cultural significance of the film is its ability to challenge conventions and promote a holistic approach to empowerment. In this approach, celibacy is portrayed as a tool for self-realization and a weapon for averting violence. The review sparkle illuminated on the junction of spirituality, female agency, and societal harmony within the film.